Dental Aspect of Distal Tubular Renal Acidosis with Genu Valgum Secondary to Rickets: A Case Report - Rakesh N. Bahadure; Nilima Thosar; Ritika Kriplani; Sudhindra Baliga; Punit Fulzele (Hindawi Limited, 2012)
Distal renal tubular acidosis is a disease that occurs when the kidneys do not remove acid properly into the urine, leaving the blood too acidic (called acidosis). Distal renal tubular acidosis (type I RTA) is caused by a defect in the kidney tubes that causes acid to build up in the bloodstream. It ultimately results rickets which include chronic skeletal pain, in skeletal deformities, skeletal fractures. Rickets is among the most frequent childhood diseases in many developing countries. Dental problems in rickets include delayed eruption of permanent teeth, premature fall of deciduous teeth, defects in structure of teeth, enamel defects in permanent teeth (hypoplastic), pulp defects, intraglobular dentine, and caries tooth. Herewith, reported a case of distal tubular renal acidosis with genu valgum secondary to rickets, with pain and extraoral swelling associated with right and left mandibular 1st permanent molars. Teeth were infected with pulp without being involved with caries. Radiographically cracks in enamel and dentin were observed. Pulp revascularization with 46 and root canal treatment was done for 36 with followup of 1 year.